Upaya Pemerintah Mengurangi Kemiskinan Dengan Program Bedah Rumah di Kota Jambi - Jevi Saputra (ILTIZAM Journal of Shariah Economics Research, 2022)
This study aims to find out how the government is alleviating poverty in Indonesia through various methods that.are continuously used to reduce poverty, one of which is the provision of various.social.assistance.to.the community.through.a.house.renovation.program. in. renovationi the. house Program.is. an .activity. carried.out in the context.of. renovating uninhabitable houses, namely residential buildings that.do not meet sanitation, safety and social requirements. The purpose.of this study is to analyze: 1) the welfare of the community.after.receiving housing repair assistance. 2) The house renovation program has an impact on reducing poverty in the city of Jambi. This study uses a qualitative approach using the qualitative data analysis method of the Miles and Huberman model. The data used is primary data with data collection methods through interviews, observation and document studies. Respondents who were interviewed were interviewed using the purposeful sampling method. The results of this study indicate that; (1) home renovation reduces the number of poor people, (2) home renovation effectively increases wealth.